Montessori and Non-Montessori Early Childhood Teachers’ Attitudes Towards Inclusion and Access - Danner, Natalie; Fowler, Susan (Journal of Montessori Research, 2015)
Montessori and non-Montessori general education early childhood teachers were surveyed about their attitudes towards including children with disabilities and providing access in their classrooms.  Both groups reported similar and positive supports for inclusion within their schools. Montessori teachers reported having less knowledge about inclusion and less special education professional development than their non-Montessori counterparts.   Implications for professional development and teacher preparation are described.